2008
DOI: 10.1007/s11250-008-9236-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different level and source of copper supplementation on immune response and copper dependent enzyme activity in lambs

Abstract: An experiment was conducted on 30 male Nellore lambs with average body weight (BW) of 15.45 +/- 0.06 kg to determine the level of the copper (Cu) supplementation in diet from inorganic and organic sources required for optimum immunity and its effect on copper dependent enzymes by allotting them randomly to five groups in completely randomized design. The dietary treatments were viz., basal diet (no Cu supplementation, BD), other four groups were offered BD supplemented with 7 or 14 ppm Cu from copper sulphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
8
1
4
Order By: Relevance
“…The results demonstrate that the use of copper preparations stimulates humoral immune mechanisms via production of activated B lymphocytes and in consequence synthesis of antibodies. Similar observations were made by Senthilkumar, Nagalakshmi, Ramana Reddy, and Sudhakar () in a study on sheep, which found that supplementation of feed with organic forms of copper increased the level of antibodies in the animals to a greater degree than copper sulphate. However, the results of some studies have been inconsistent.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results demonstrate that the use of copper preparations stimulates humoral immune mechanisms via production of activated B lymphocytes and in consequence synthesis of antibodies. Similar observations were made by Senthilkumar, Nagalakshmi, Ramana Reddy, and Sudhakar () in a study on sheep, which found that supplementation of feed with organic forms of copper increased the level of antibodies in the animals to a greater degree than copper sulphate. However, the results of some studies have been inconsistent.…”
Section: Discussionsupporting
confidence: 85%
“…An increase in the activity of this enzyme induced by administration of an organic form of copper has been demonstrated by Xin, Waterman, Hemken, and Harmon () in cattle and by Senthilkumar et al. () in sheep. In contrast, Koh, Peng, and Klasing () and Dorton et al.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Senthilkumar P reported that the total immunoglobulin concentration and the cell-mediated immune response against PHA-P and Con-A was higher in lambs fed 14 ppm Cu-proteinase diet. The IgM level was though high in Cu supplemented lambs [33]. Lead (Pb) was found in at an average level of 0.852 mg/kg.…”
Section: Resultsmentioning
confidence: 98%
“…As the component of several enzymes such as Cu/Zn-SOD [24], Cu at an appropriate dosage may decrease lipid peroxidation by increasing the activity of antioxidant enzymes [25,26]. The degree of lipid peroxidation could be evaluated by MDA [27].…”
Section: Discussionmentioning
confidence: 99%